Perceptions of appropriate treatment among the informal allopathic providers: Insights from a qualitative study in two peri-urban areas in Bangladesh - Sizear, M. Monaemul Islam; Nababan, Herfina Y.; Bin Siddique, Md. Kaoser; Islam, Shariful; Paul, Sukanta; Paul, Anup Kumar; Ahmed, Syed Masud (BMC, 2022)
This article was published in the BMC Health Services Research [© The Author(s). 2019 Open Access This article is distributed under the terms of the Creative Commons Attribution 4.0 International License (http://creativecommons.org/licenses/by/4.0/)] and the definite version is available at: https://doi.org/10.1186/s12913-019-4254-3 The Journal's website is at: https://bmchealthservres.biomedcentral.com/articles/10.1186/s12913-019-4254-3#citeas